Impact of antiplatelet therapy on microvascular thrombosis during ST-elevation myocardial infarction - Khattak, Sophia; Townend, Jonathan N.; Thomas, Mark R. (Frontiers in Molecular Biosciences, 2024)
During an acute coronary syndrome, atherosclerotic plaque rupture triggers platelet activation and thrombus formation, which may completely occlude a coronary artery leading to ST-elevation myocardial infarction (STEMI). Although emergency percutaneous coronary intervention (PCI) is effective in re-opening the main coronary arteries, the downstream microvasculature can become obstructed by embolised plaque material and thrombus. Dual antiplatelet therapyis recommended by guidelines and used routinely for the management of STEMI to reduce the risk of recurrent atherothrombotic events. However it is unclear to what extent antiplatelet therapy reduces microvascular thrombosis, largely because most tools to assess microvascular thrombosis only became available after antiplatelet therapy was already used in the majority of patients. Platelets play a central role in key aspects of microvascular thrombosis, such as atherosclerotic plaque-induced thrombus development, inflammation and microvascular dysfunction, making them a potential target for novel therapeutic interventions. Currently, more potent antiplatelet agents like GPIIb/IIIa inhibitors may be administered during PCI directly into coronary arteries with high thrombus burden but it is not well-established whether this reduces microvascular thrombosis and they significantly increase the risk of bleeding. In this review article we discuss the role of platelets in microvascular thrombosis, describe how microvascular thrombosis and obstruction can be assessed clinically and explore potential new antiplatelet treatments for this. In particular, we highlight novel antiplatelet drugs targeting the platelet receptor GPVI, as well as PAR4, GPIb-IX-V and 5HT2A receptors. We also discuss the potential benefit of P-selectin inhibitors as they have proven to be effective in reducing microvascular thrombosis in sickle-cell disease which could translate into potential benefits in acute coronary syndrome.